Preparation and evaluation of zeolites for ammonium removal from municipal wastewater through ion exchange process - Guida, Samuela; Potter, Chris; Jefferson, Bruce; Soares, Ana (Nature Research (part of Springer Nature), 2020)
The application of ion exchange process for ammonium (NH4+-N) removal from wastewater is limited due to the lack of suppliers of engineered zeolites which present high ammonium exchange capacity (AEC) and mechanical strength. This study focuses on the preparation and evaluation of synthetic zeolites (Zeolite1-6) by measuring AEC and resistance to attrition and compression, against natural (clinoptilolite) and engineered zeolite (reference, Zeolite-N). At high NH4+-N concentrations, Zeolite6 and Zeolite2 showed capacities of 4.7 and 4.5 meq NH4+-N/g media, respectively. In secondary effluent wastewater (initial NH4+-N of 0.7 meq NH4+-N/L), Zeolite1, 2 and 6 showed an AEC of 0.05 meq NH4+-N/g media, similar to Zeolite-N (0.06 meq NH4+-N /g media). Among the synthetic zeolites, Zeolite3 and 6 showed higher resistance to attrition (disintegration rate = 2.7, 4.1 NTU/h, respectively) when compared with Zeolite-N (disintegration rate = 13.2 NTU/h). Zeolite4 and 6 showed higher resistance to compression (11 N and 6 N, respectively). Due its properties, Zeolite6 was further tested in an ion exchange demonstration scale plant treating secondary effluent from a municipal wastewater treatment plant. However, Zeolite6 disintegrated after 2 months of operation, whilst Zeolite-N remained stable for 1.5 year. This highlighted the importance of the zeolite’s mechanical strength for successful application. In particular, future work should focus on the optimization of the zeolite production process (temperature, time and dimension of the kiln during calcination) to obtain an engineered zeolite with a spherical shape thus reducing eventual sharp edges which can affect mechanical strength